An all-in-one nanoparticle (AION) contrast agent for breast cancer screening with DEM-CT-MRI-NIRF imaging. Issue 36 (7th September 2018) - Hsu, Jessica C.; Naha, Pratap C.; Lau, Kristen C.; Chhour, Peter; Hastings, Renee; Moon, Brianna F.; Stein, Joel M.; Witschey, Walter R. T.; McDonald, Elizabeth S.; Maidment, Andrew D. A.; Cormode, David P.
Abstract : AION have improved biocompatibility and are an effective multimodal contrast agent for breast cancer diagnosis. Abstract : Conventional X-ray mammography has low diagnostic sensitivity for women with dense breasts. As a result, alternative contrast-enhanced screening tools such as dual energy mammography (DEM), computed tomography (CT), magnetic resonance imaging (MRI), and near-infrared fluorescence (NIRF) imaging are being used or investigated for these women. However, currently available contrast agents are non-ideal, have safety issues, and each imaging technique requires a different contrast agent. We therefore sought to develop a multimodal contrast agent that is functional for each breast imaging modality to simplify the diagnosis process and address the issues of existing contrast agents. Herein, we present a novel "all-in-one" nanoparticle (AION) multimodal imaging probe that has potent DEM, CT, MRI, and NIRF contrast properties and improved biocompatibility. AION were formed by co-encapsulation of a near-infrared fluorophore (DiR), silver sulfide nanoparticles (Ag2 S-NP), and iron oxide nanoparticles (IO-NP) in PEGylated micelles. AION showed negligible cytotoxicity, which was in agreement with its minimal silver ion release profiles. AION generated strong contrast with all imaging modalities as demonstrated in phantom imaging. AION allowed in vivo tumor imaging as evidenced by the increase in contrast after injection. This study indicates the potential of AION as an effective multimodal contrast agent for breast cancer diagnosis with a range of imaging methods.